2009
DOI: 10.1007/s00497-009-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of APETALA2 on embryo, endosperm, and seed coat development determine seed size in Arabidopsis

Abstract: Arabidopsis APETALA2 (AP2) controls seed mass maternally, with ap2 mutants producing larger seeds than wild type. Here, we show that AP2 influences development of the three major seed compartments: embryo, endosperm, and seed coat. AP2 appears to have a significant effect on endosperm development. ap2 mutant seeds undergo an extended period of rapid endosperm growth early in development relative to wild type. This early expanded growth period in ap2 seeds is associated with delayed endosperm cellularization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 42 publications
6
144
0
1
Order By: Relevance
“…These studies allowed us to identify AP2 as an important regulator of fruit patterning in Arabidopsis. Although AP2 had been extensively studied with respect to its roles in flower, ovule and seed development Drews et al, 1991;Aukerman and Sakai, 2003;Chen, 2004;Ohto et al, 2009), little is known about the involvement of AP2 in Arabidopsis fruit morphogenesis. Our studies show that AP2 acts to prevent valve margin and replum overgrowth by negatively regulating the expression of valve margin and replum identity genes (Fig.…”
Section: Ap2 Controls the Development Of Replum And Valve Margin Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies allowed us to identify AP2 as an important regulator of fruit patterning in Arabidopsis. Although AP2 had been extensively studied with respect to its roles in flower, ovule and seed development Drews et al, 1991;Aukerman and Sakai, 2003;Chen, 2004;Ohto et al, 2009), little is known about the involvement of AP2 in Arabidopsis fruit morphogenesis. Our studies show that AP2 acts to prevent valve margin and replum overgrowth by negatively regulating the expression of valve margin and replum identity genes (Fig.…”
Section: Ap2 Controls the Development Of Replum And Valve Margin Tissuesmentioning
confidence: 99%
“…The AP2 gene is known to be post-transcriptionally regulated by microRNAs (Aukerman and Sakai, 2003;Chen, 2004). In addition to its role in flower organ identity (Bowman et al, 1989;Bowman et al, 1991;Drews et al, 1991;Jofuku et al, 1994;Kunst et al, 1989), AP2 is known to regulate flowering time, shoot apical meristem maintenance and seed development (Jofuku et al, 1994;Jofuku et al, 2005;Mathieu et al, 2009;Ohto et al, 2005;Ohto et al, 2009;Würschum et al, 2006;Yant et al, 2010), although the role of AP2 in fruit development has not been described in detail. During the preparation of this manuscript, two independent studies identified that SlAP2a, the true ortholog of AP2 in tomato, controls fruit ripening via regulation of ethylene biosynthesis and signaling (Chung et al, 2010;Karlova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…AP2 is involved in a great variety of 160 developmental processes, including endosperm cellular-161 ization. ap2 mutant seeds undergo an extended endosperm 162 proliferation stage, associated with a delay in cellulariza-163 tion (Ohto et al 2009). Additionally, the abnormal endo-164 sperm development in ap2 mutants resulted in other seed 165 defects, such as enlarged embryos that show increased cell 166 number and cell size (Jofuku et al 2005;Ohto et al 2005).…”
mentioning
confidence: 99%
“…The AP2, Zincfinger protein and MYB are regulatory genes for many plant stress responses. The AP2/EREBP is the largest plant TF family and they play an important role for regulating responses for abiotic or biotic stresses and for a number of plant developments (Ohto et al, 2009). A number of NAC protein are also involved in plant responses to stress (Delessert et al, 2005).…”
Section: Resultsmentioning
confidence: 99%